The Effect of Profitability and Banking Financial Performance on Corporate Social Responsibility (CSR) Disclosure in Banking Companies Listed on the Indonesia Stock Exchange (IDX) - chuanta, gracy; Linda Wahyu Marpaung (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine whether the effect of profitability and financial performance has a significant effect on CSR disclosure in banking companies listed on the Indonesia Stock Exchange (IDX) This study uses quantitative methods and multiple linear regression analysis methods. The population in this study comes from data listed on the IDX in 2020-2023. The sampling technique used purposive sampling. Data analysis and testing consists of descriptive statistics, classical assumption tests, multiple linear regression analysis, partial (T test) and simultaneous (F test) hypothesis testing, and the coefficient of determination test (R² test). Partial research results show the effect of profitability has no effect on CSR disclosure. The effect of financial performance has a significant effect on CSR disclosure. Based on the results of simultaneous hypothesis testing, it is known that the results of the F test show that profitability and financial performance variables have a significant effect on CSR disclosure.